HADITHS ABOUT THE VALUE OF EDUCATION ABOUT THE CREED - Rizka Amalia Rahmadhani; Ira Suryani (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
ABSTRACTChildren are born with nature, parents are obliged to maintain and save this nature. so what is the value of education contained in the hadith of al-Bukhari, so that we can know the value of education in this hadith is in terms of the value of faith education, children who are born have the nature of the religion of monotheism, namely Islam.